Implementation of the Merdeka Curriculum at SD Muhammadiyah 22 Surabaya: Challenges and Opportunities - Milatun Nadifa (Postgraduate Program Magister Pendidikan Agama Islam, 2025)
This research aims to analyze the implementation of the Merdeka Curriculum at SD Muhammadiyah 22 Surabaya, focusing on the challenges and opportunities encountered by teachers, particularly in developing 21st-century competencies. In the context of globalization and the Fourth Industrial Revolution, education faces pressure to adapt quickly and effectively. The study employs a qualitative descriptive approach to investigate teachers' perceptions of the Merdeka Curriculum implementation at SD Muhammadiyah 22 Surabaya. Within this context, the Threats-Weaknesses-Opportunities-Strengths (TWOS) Analysis is used to underscore minimizing weaknesses and threats faced by schools in the Merdeka Curriculum implementation context. The research findings reveal that the implementation of the Merdeka Curriculum at SD Muhammadiyah 22 Surabaya faces the challenge of teachers' limited understanding of key concepts, particularly in developing 21st-century competencies. TWOS Analysis highlights the need for effective follow-up strategies, continuous professional training, and principal support to create a conducive learning environment. SD Muhammadiyah 22 Surabaya's proactive efforts in overcoming these challenges indicate the potential to enhance curriculum implementation effectiveness, fostering a stimulating learning environment for students to navigate the complexities of the modern world.